Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10103-015-1753-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two lasers on the polymerization of composite resins: single vs combination

Abstract: The selection of a light-curing unit for the curing composite resins is important to achieve best outcomes. The purpose of the present study was to test lasers of 457 and 473 nm alone or in combination under different light conditions with respect to the cure of composite resins. Four different composite resins were light cured using five different laser combinations (530 mW/cm(2) 457 nm only, 530 mW/cm(2) 473 nm only, 177 mW/cm(2) 457 + 177 mW/cm(2) 473 nm, 265 mW/cm(2) 457 + 265 mW/cm(2) 473 nm, and 354 mW/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Nevertheless, with lasers and laser modulation becoming more affordable, the most modern developments using diode lasers also exploit this trend and aim to further reduce curing time (1 s for 2.5 mm) through much higher power outputs (~1.4-2.0 W) and supposedly provide more consistent dispersion of energy and power at any distance (e.g. Monet, introduced in 2021) with the manufacturers claiming more reliable, more homogenous and complete cure through depth [29,30,34,45,95]. Indeed, these claims need to be confirmed and only likely to be valid under certain conditions due to limitations in materials chemistry and physics which suggest that the process of curing dental materials is a quantum process and strictly not dependent on the energy delivered to the surface [60,94].…”
Section: High Irradiance Curingmentioning
confidence: 99%
“…Nevertheless, with lasers and laser modulation becoming more affordable, the most modern developments using diode lasers also exploit this trend and aim to further reduce curing time (1 s for 2.5 mm) through much higher power outputs (~1.4-2.0 W) and supposedly provide more consistent dispersion of energy and power at any distance (e.g. Monet, introduced in 2021) with the manufacturers claiming more reliable, more homogenous and complete cure through depth [29,30,34,45,95]. Indeed, these claims need to be confirmed and only likely to be valid under certain conditions due to limitations in materials chemistry and physics which suggest that the process of curing dental materials is a quantum process and strictly not dependent on the energy delivered to the surface [60,94].…”
Section: High Irradiance Curingmentioning
confidence: 99%
“…Even if blue laser was previously proposed in dentistry field for composite resin polymerization, while argon laser showed its efficacy, diode lasers apparently are not proposed as useful for this use[ 27 - 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 As described earlier, the first indication for the use of blue laser in dentistry was the composite resin polymerization; in fact, while the studies performed by argon laser demonstrated its efficacy, results obtained by diode laser seem to be not encouraging. [27][28][29][30][31] Blue diode laser has recently been proposed, coupled to titanium oxide, for dental bleaching. 32 The aim of this ex vivo work was to analyze the effectiveness of five different fiber-delivered laser wavelengths (450, 532, 808, 1064, and 1340 nm) in oral surgery on animal models by recording surface and deep temperatures, speed of cut, and histological changes.…”
Section: Introductionmentioning
confidence: 99%